Management of Short Cervix during Pregnancy: A Review - Gilner, Jennifer; Biggio, Joseph (American Journal of Perinatology, 2016)
Sonographic evaluation of the uterine cervix has evolved as one of the best clinical tools available for the prediction of subsequent spontaneous preterm birth (PTB), particularly when combined with prior poor obstetric history. There is a growing body of evidence describing interventions for short cervix that reduce the risk of preterm delivery and improve neonatal outcomes. Yet, given the significant heterogeneity in the pathways that lead to PTB, understanding the specific clinical characteristics of women who may benefit from a given intervention is critical to appropriate implementation. The three primary management strategies that have demonstrated improvement in obstetric and/or perinatal outcomes for appropriately selected women with a sonographically short cervix (vaginal progesterone, cervical cerclage, and pessary) are the subject of this review. In addition, the unique considerations of multiple pregnancies are discussed separately from singletons.
Keywords: preterm birth; short cervix; cervical insufficiency; progesterone; cervical cerclage; cervical pessary